Influence of Cooling Rate on Crack Growth and Stress Distribution in Die Steel under Thermal Cycles - Yao, Lei (International Journal of Mechanical and Electrical Engineering, 2024)
Die casting molds are prone to thermal fatigue under high-temperature and high-pressure cycles, which significantly affects their service life. In this study, a three-dimensional numerical simulation method is employed to analyze the temperature field, stress field, and crack development process of the mold under different cooling cycles. The results show that shorter cooling cycles (15s, 30s) lead to larger temperature gradients and stress concentrations within the mold, thereby accelerating crack initiation and propagation. In contrast, longer cooling cycles (70s) help to reduce the temperature gradient and stress fluctuations, which in turn slows down crack propagation and effectively extends the mold’s service life.